1988
DOI: 10.2135/cropsci1988.0011183x002800030015x
|View full text |Cite
|
Sign up to set email alerts
|

Heterotic Patterns among Ten Corn Belt and Exotic Maize Populations

Abstract: Maize breeders are concerned with the narrow base of Corn Belt germplasm and the wide use of one heterotic pattern, ‘Reid’ × ‘Lancaster’, in maize (Zea mays L.). Knowledge of other heterotic patterns can contribute to a broadening of the commercial germplasm base. The study was carried out to evaluate heterotic combinations among seven yellow‐endosperm populations—‘BSSS(R)C10’,‘BSK(HI)C8 Syn 3’, ‘BS16(S)C3 Syn 2’, ‘Mexican Dent’, ‘Leaming’, ‘Midland’, among three white‐endosperm populations—‘Pride of Sameline’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
5

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 0 publications
4
42
0
5
Order By: Relevance
“…Sprague noted "it appears that the ear-to-row method of selection for yielding ability was discredited not because of genetic limitations of the method, but because of the inadequate field plot technique" [16]. Research after Richey's 1922 conclusion showed recurrent selection and varietal hybrids could be very successful at increasing maize yields after all, although they could not provide cultivars with the yields of the best hybrids [35,47,81,95,119,120,[126][127][128][129][130][131].…”
Section: Recurrent Selection Revisitedmentioning
confidence: 99%
See 1 more Smart Citation
“…Sprague noted "it appears that the ear-to-row method of selection for yielding ability was discredited not because of genetic limitations of the method, but because of the inadequate field plot technique" [16]. Research after Richey's 1922 conclusion showed recurrent selection and varietal hybrids could be very successful at increasing maize yields after all, although they could not provide cultivars with the yields of the best hybrids [35,47,81,95,119,120,[126][127][128][129][130][131].…”
Section: Recurrent Selection Revisitedmentioning
confidence: 99%
“…Advantages of this approach could be higher yields than possible with populations per se, cheap hybrid seed given the levels of production that may be possible with populations compared to expected yields of inbred parent lines, and the possibility for ongoing improvement of the parent populations and their hybrids on-farm. Disadvantages could include separate seed production requirements, likely lower yield than single cross hybrids [129], and lower uniformity than that observed in single cross hybrids.…”
Section: Composite and Synthetic Populations As Op Cultivarsmentioning
confidence: 99%
“…According to Crossa et al (1990), in the Americas there is a tremendous genetic diversity in maize, as a result of thousands of years of evolution under domestication and hybridization, which has not been effectively exploited. Many authors have suggested the usefulness of incorporating exotic germplasm into breeding programs (Eberhart 1971, Hallauer and Miranda 1981, Oyerbides-Garcia et al 1985, Holley and Goodman 1988, Mungoma and Pollak 1988, Iglesias and Hallauer 1989, Pollak et al 1991, Michelini and Hallauer 1993, Rodrigues and Chaves 2002, Carena 2005, Soengas et al 2006. Thompson (1968) found that a group of exotic and semi-exotic populations yielded on average 28% more digestible dry matter than adapted hybrids, and Stuber LC Gabriel et al (1986) suggested that some semi-exotic materials might be suitable for silage, given their good grain production and great vegetative development.…”
Section: Introductionmentioning
confidence: 99%
“…Most results relate to the usefulness of crosses between exotic x adapted germplasm (Eberhart, 1971;Gerrish, 1983;Oyervides-Garcia et al, 1985;Holland and Goodman, 1995), the estimates of genetic parameters (Goodman, 1965;Hallauer and Sears, 1972;Sheata and Dhawan, 1975;Santos and Miranda Filho, 1992), and the determination of heterotic patterns (Holley and Goodman, 1988;Mungoma and Pollak, 1988;Pollak et al, 1991;Godshalk and Kauffmann, 1995;Uhr and Goodman, 1995;Eschandi and Hallauer, 1996).…”
Section: Introductionmentioning
confidence: 99%